Analisis Aspek Konteks, Input, Proses, Produk Pelayanan Telemedicine Pada Masa Pandemi Covid-19 (Studi Kasus : Rumah Sakit Ortopedi Prof. Dr. R. Soeharso Surakarta) - Rizqi Annisa Nur Fananni; Putri Asmita Wigati; Nurhasmadiar Nandini (Jurnal Manajemen Kesehatan Indonesia, 2022)
ABSTRACTBackground: The existence of the Covid-19 pandemic that hit the whole world, especially in Indonesia, had a significant impact on the health sector, especially in the provision of health services for the community. With this condition, the Indonesian government began to develop long-distance services (Telemedicine), where these services are aimed at preventing the spread of Covid-19, especially in health care facilities, as well as providing convenience for the community to reach health services during the Covid-19 pandemic. Of several hospitals in Surakarta, Prof. Dr. R. Soeharso Orthopedic Hospital is one of the hospitals that develops telemedicine services during the Covid-19 pandemic. From this, an overall analysis is needed regarding the implementation of telemedicine services whether they are appropriate and can achieve their goals and have a significant level of use and impact during the Covid-19 pandemic. Thus, this study aims to analyze the context, input, process, and product aspects of telemedicine services during the Covid-19 pandemic. Method: This research was conducted using the CIPP theory by Daniel L. Stufflebeam (1966) which consists of aspects of context, input, process, and product. This study uses qualitative research methods with data collection carried out by in-depth interviews selected based on purposive sampling.Results: The results showed that the operation of telemedicine services was carried out due to the Covid-19 pandemic condition with the aim of providing complete services to patients during the Covid-19 pandemic, lack of socialization regarding guidelines for implementing telemedicine to related implementing staff, poor coordination in the planning process, the inclusion of telemedicine into the annual and five-year planning of the Prof. Dr. R. Soeharso Orthopedic, there is no report to the authorities regarding telemedicine services, there is no patient satisfaction survey regarding the telemedicine services provided.